More than ‘more than ever’: Revisiting a work design and sociotechnical perspective on digital technologies - Parker, Sharon; Grote, G. (WILEY, 2022)
We respond to commentaries on our 2020 article ‘Automation, algorithms, and beyond: Why work design matters more than ever in a digital world’ and report on research on the topic since that publication. A top-down work design perspective on digital technologies appears even more important than ever yet still neglected, as suggested by recent studies. The opportunities and challenges of new technologies have been addressed somewhat more successfully through bottom-up work design in the form of job crafting. The specific topic of virtual working has also attracted significant research attention. Nevertheless, we continue to advocate more scholarly and practical attention to the following: how to proactively redesign work when introducing new technologies; how work design issues can be built into the design and procurement of work technologies; the need to identify and understand both the organizationally oriented strategies and macro-level change needed for successful sociotechnical application; and how to upskill employees, managers, unions and other stakeholders, in work design and related topics. There is also more scope for consideration of the role of individual differences. Finally, we call for interdisciplinary research that involves, for example, the designers of technology, and we advocate the importance of intervention studies.